2015
DOI: 10.3727/096368914x679363
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Insulin-Secreting Porcine Bone Marrow Stromal Cells Ex Vivo and Autologous Cell Therapy in Vivo

Abstract: Cell therapy could potentially meet the need for pancreas and islet transplantations in diabetes mellitus that far exceeds the number of available donors. Bone marrow stromal cells are widely used in clinical trials mainly for their immunomodulatory effects with a record of safety. However, less focus has been paid to developing these cells for insulin secretion by transfection. Although murine models of diabetes have been extensively used in gene and cell therapy research, few studies have shown efficacy in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 64 publications
(73 reference statements)
0
6
0
Order By: Relevance
“… BMSCs from fresh bone marrow were cultured in a 3:1 (v/v) mixture of low‐glucose Dulbecco's modified Eagle's medium (Invitrogen, Carlsbad, CA, USA) as previously described . BMSCs were expanded in culture for 3 weeks after bone marrow aspiration.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… BMSCs from fresh bone marrow were cultured in a 3:1 (v/v) mixture of low‐glucose Dulbecco's modified Eagle's medium (Invitrogen, Carlsbad, CA, USA) as previously described . BMSCs were expanded in culture for 3 weeks after bone marrow aspiration.…”
Section: Resultsmentioning
confidence: 99%
“…D, Flow cytometry profile of GFP‐positive primary BMSCs of dog #5954 (intramedullary implantation) 24 h after electroporation with a GFP‐expressing plasmid. E, A representative profile of positive and negative markers of mesenchymal stromal cells present in early passage BMSCs in this study analysed by flow cytometry as previously described . Broken lines denote the corresponding isotype control.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors reported that hyperglycemia was normalized within 3-4 days and maintained for several months, which was astonishing since it followed a xenogeneic transplantation without immunoisolation or immunosuppression. Thi Do and associates transfected porcine bone marrow-derived MSCs with the insulin gene using a lentiviral vector [70]. Autologous transplantation of the treated cells in the liver of pigs with STZ-induced diabetes resulted in partial improvement of their hyperglycemia.…”
Section: Genetic Transfectionmentioning
confidence: 99%